2017
DOI: 10.1111/jasp.12456
|View full text |Cite
|
Sign up to set email alerts
|

Looking forward to helping: The effects of prospection on prosocial intentions and behavior

Abstract: Three experiments were conducted to further examine how prospection (i.e., thinking about the future) fosters prosociality. In Study 1 (n = 238), participants who wrote about the future expressed significantly stronger prosocial intentions than people who wrote about the past. In a similar study (n = 87), participants who wrote about the future were significantly more likely to behave prosocially than those who wrote about the past. In Study 3 (n = 203), mediational analyses revealed that prospection and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
1
8
0
1
Order By: Relevance
“…This finding is in line with evidence that people striving for future goals and rewards are more likely to engage in prosocial behavior [ 45 ]. Coherent with our findings, two experimental studies on future-oriented thinking found that participants who performed a writing task on their future life plans reported higher intentions to help others than participants who wrote about their present daily routine [ 19 ] or about past general or prosocial activities [ 46 ]. Writing about future life plans may induce goal setting and pursuit, which is an inherent aspect of focusing on remaining opportunities [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…This finding is in line with evidence that people striving for future goals and rewards are more likely to engage in prosocial behavior [ 45 ]. Coherent with our findings, two experimental studies on future-oriented thinking found that participants who performed a writing task on their future life plans reported higher intentions to help others than participants who wrote about their present daily routine [ 19 ] or about past general or prosocial activities [ 46 ]. Writing about future life plans may induce goal setting and pursuit, which is an inherent aspect of focusing on remaining opportunities [ 6 , 16 ].…”
Section: Discussionsupporting
confidence: 80%
“…Results show a strong relationship between optimism and gratitude. This is especially relevant considering that a recent literature review indicates that thinking about the future could promote prosociality (Maki et al, 2016;Baumsteiger, 2017). In addition, variables related to prosociality like gratitude, which promotes self-transcendence, seem to be key to human well-being (Schwartz and Sortheix, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, prosociality has been hypothesized as a basic psychological need for the human being (Martela and Ryan, 2016), which would be complementary to the other three needs (relatedness, autonomy, and competence) comprised by the Self-Determination Theory (SDT) (Ryan and Deci, 2000). Therefore, over the last years, increasing attention has been paid to how prospective variables like optimism are related to prosociality (Baumsteiger, 2017). In a recent study conducted by Maki et al (2016), the authors concluded that prospection promotes prosocial intentions and consequently increases the probability that people help others.…”
Section: Optimism Prosociality and Meaning In Lifementioning
confidence: 99%
“…For example, Milfont et al (2012) found that individuals with a future time perspective tend to exhibit higher pro-environmental behaviors, while Bruderer Enzler (2014) identified consideration of future consequences as a significant predictor of pro-environmental behavior. Similarly, Baumsteiger (2017) conducted three experiments and found that future-oriented individuals were more likely to behave prosocially. Moreover, related to the context of this study, future-oriented individual also tend to care more about health status and health behaviors, as demonstrated in the panel study of Kehana et al (2006) and the online survey research of Griva et al (2014).…”
Section: Temporal Focus Theorymentioning
confidence: 99%